ANALISIS KINERJA TENAGA KEPENDIDIKAN DIREKTORAT KEMITRAAN, ALUMNI, DAN URUSAN INTERNASIONAL UNIVERSITAS GADJAH MADA - Dea Eka Martshita; Ivo Novitaningtyas (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2019)
This research aims to analyzing the effect of organizational climate and job satisfaction on employee performance with organizational commitment as intervening variable on staff of Directorate of Partnership, Alumni, and Global Initiatives of Universitas Gadjah Mada (DKAUI UGM). The population in this study amounted to 57 employee using the census method. The data was analyzing based on Partial Least Square with SmartPLS 2.0 M3 program, and Sobel Test to prove organizational commitment variable as an intervening variable. The results of the research indicate that: 1) Organizational climate has a direct and significant positive effect on employee performance on staff of DKAUI UGM; 2) Job satisfaction has a direct and significant positive effect on employee performance on staff of DKAUI UGM; 3) Organizational climate effects positively and indirectly positively to employee performance with organizational commitment as intervening variable on staff of DKAUI UGM; 4) Job satisfaction has an indirect and significant positive effect on employee performance with organizational commitment as intervening variable on staff of DKAUI UGM.